Praktik Jual Beli Pada Agrowisata Petik Buah Jeruk Di Desa Waru Kecamatan Palang Kabupaten Tuban Perspektif Hukum Islam - Habib Masyhudi; Zulfa Imroatus Shofiyah (MASADIR: Jurnal Hukum Islam, 2022)
Tuban is one of the districts supporting the national food storage in East Java, where there are tourist attractions for citrus fruit picking gardens. Agriculture-based tourism will provide great opportunities for farmers and communities to expand the agricultural sector and increase income. The agro-tourism system for picking oranges in Waru Village, Palang District, Tuban Regency, is that every visitor who wants to enter an orange garden does not have an entry ticket, but is required to buy the fruit. Here the author is interested in researching this practice from the perspective of Islamic law. This study uses a qualitative method, data collection is done through interviews, observation, documentation, and meaning. The results of the analysis of buying and selling practices in citrus fruit picking agro-tourism concluded that buying and selling practices there did not meet the requirements in the specified buying and selling, namely the conditions of aqid (a person who has a contract), which should be the requirements of an aqid being baligh, intelligent, tamyyiz and without coercion, while on the other hand there is no opportunity for the buyer to cancel if he has agreed to the contract for granting permission to enter with these conditions. According to the Malikiyah and Hanafiyah scholars, a sale and purchase that has not fulfilled one of the terms and pillars means that the contract is classified as a vanity contract and the fiqh scholars state that a false contract is classified as an invalid contract..